6y+78=2(67-4y)

Simple and best practice solution for 6y+78=2(67-4y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y+78=2(67-4y) equation:



6y+78=2(67-4y)
We move all terms to the left:
6y+78-(2(67-4y))=0
We add all the numbers together, and all the variables
6y-(2(-4y+67))+78=0
We calculate terms in parentheses: -(2(-4y+67)), so:
2(-4y+67)
We multiply parentheses
-8y+134
Back to the equation:
-(-8y+134)
We get rid of parentheses
6y+8y-134+78=0
We add all the numbers together, and all the variables
14y-56=0
We move all terms containing y to the left, all other terms to the right
14y=56
y=56/14
y=4

See similar equations:

| 1x/4+3=3x/4-7 | | 45+(-9)=13n+(-7n | | -7r-3=9-4r | | 3/x-6=-45 | | y=3÷5×+1 | | 4(x+2)=7x-13 | | 7n+7+8=-20 | | 355-5m=(355-5m) | | 5(x-3)=8-4(x-1) | | 355-5m=(355-5m)/2 | | 13− 28x =4+ 8x | | n/2=n+3/4 | | 38+37=9w+(+6w) | | S=30-r30 | | 3(x+4)-4-2x=5 | | 8x+1=-8+3(x+3) | | 355-5m=0-0m | | S=30-r(30) | | -2x+18=11x-8 | | -23=-2+3v | | 15=5/6y | | 2.53=-2.3x | | -2p+4=8-4p | | 5x=3.75 | | 8x+1=-8+39x+30 | | 8-2(n+1)=6-9n | | 5*x+4*B=35 | | 4x^2+128x-224=0 | | -0.25w+7-0.75w=-2 | | 52x-21=3x+7(7x+3) | | 10m-2/5=9.03/5 | | -16x^2+320x+25600=0 |

Equations solver categories